An insight into solar thermo-assisted and organic-molecule alternated water splitting chemistry for hydrogen production and wastewater treatment by elucidating redox model and thermodynamics. (15th December 2020) - Wang, Baohui; Jiang, Hong; Gu, Di; Li, Chaoying; Nie, Chunhong; Yan, Chao; Yuan, Dandan; Wang, Xirui
Highlights: The efficient solar system was proposed for enabled hydrogen and water treatment. The redox model and theoretical calculation were conducted for the solar system. The action results in a negative temperature coefficient to the cell potential. The thermodynamics proves the potential decreases and half-reaction switch. Abstract: Three research hotspots in today's world have been endowed with renewable solar energy, wastewater treatment and hydrogen production. Focused on the intersection of the three hotspots, solar-driven thermal & donor modulated electrolytic water splitting to hydrogen production plus wastewater treatment was constructed for efficient hydrogen production and effective wastewater treatment. The system was facilitated by an action of a solar highly thermal coupling and donor-alternative to the redox chemistry. For a motivation of totally elucidating the solar thermo-assisted and organic donor-alternated water splitting system, the redox model and thermodynamic calculation were first conducted in this paper, based on the combination of the electrochemical and thermodynamic equations of the hydrogen production complex. The redox models fully demonstrate that the prevailing and dominant reactions occur in the alternative of the complex organic donors, fed in soluble small organic molecules in wastewater such as small organic alcohol, aldehyde, and acid. The results novelly showed that the oxygen evolution reaction on the anode was found to be replaced by the alternative of the easily electron-donated molecules to dominate the anodic reaction of the organics to carbon dioxide. The calculated thermo-dependent potentials reveal that the thermo-assisted action results in a negative temperature coefficient to the cell potential. The thermodynamic calculation theoretically proves that the electrolytic potential is sharply reduced by a switch of the anodic reaction and thermo-assisted effect. Therefore, both thermal assistance and organic donor alternation give fall to the cell potential (from 1.229 V to 0.4–0.6 V) and switch from the oxygen evolution reaction to the anodic oxidation of organic molecules. The operated cell potentials are predicted reasonably more than the applied voltage required for the endothermic water-splitting redox, nearly no H2 evolution in such a range of the applied bias. The data can be applied for the organic donor choice and temperature modulation for the promotion of the hydrogen production. The data could offer theoretical support for solar-enabled hydrogen production and water treatment.